Influence of illness perception on depression and anxiety in individuals with schizophrenia during the COVID-19 pandemic - Zhang, Meng; Deng, Yan-Feng (Frontiers in Public Health, 2025)
ObjectiveThis study aimed to investigate the factors influencing depression and anxiety in individuals with schizophrenia during the COVID-19 pandemic, with the goal of providing evidence to support strategies for improving emotional disturbances during the pandemic.MethodsA cross-sectional study was conducted among 159 outpatients with schizophrenia between January and June 2023. Data were collected using a self-developed sociodemographic questionnaire, the Chinese version of the Illness Perception Questionnaire-Revised (IPQ-R), the Patient Health Questionnaire-9 (PHQ-9), and the 7-item Generalized Anxiety Disorder scale (GAD-7). Regression analysis was performed using SPSS version 27.0 to identify the factors associated with depression and anxiety.ResultsTimeline cyclical and treatment control were significant predictors of depression among individuals with schizophrenia (R2 = 0.160, p < 0.01). Additionally, timeline cyclical and the presence of chronic comorbidities significantly predicted anxiety (R2 = 0.217, p < 0.01).ConclusionIllness perception concerning COVID-19 significantly influenced the severity of depression and anxiety in individuals with schizophrenia. Addressing these perceptions serves as an essential component of interventions aimed at improving mental health outcomes during the pandemic.